Identification with Place and Place Identity: The Perspective of the Mental Maps of the Inhabitants of Enclaves of Poverty - Marcjanna Nóżka (Przeglad Socjologii Jakosciowej, 2023)
Enclaves of poverty are spaces of social stigmatization that can foster exclusion as well as enhance the impression of it. At the same time, they are milieus in the lives of specific human beings who co-inhabit and co-create these spaces; they are a home base – a place of safety, one that is the source of satisfaction and identification. The circumstances constituting and distinguishing these specific ecosystems were the inspirations for research conducted in 2014–2016 in enclaves of poverty – located in two large cities and in rural areas in Poland – to identify the ways of valuing and mental mapping performed by people living there. Based on the results of the author’s research, the article discusses three complementary issues covering the ways of identifying a space, identifying with a place and place identity. It focuses on the cognitive and practical value of such findings, which go beyond simplified and generalized thinking about enclaves of poverty, revealing the potentials of various neighbourhoods and the complexity of people’s connections with a place.